Novel PPAR pan agonist, ZBH ameliorates hyperlipidemia and insulin resistance in high fat diet induced hyperlipidemic hamster. - Wei Chen; Shiyong Fan; Xinni Xie; Nina Xue; Xueyuan Jin; Lili Wang (PLoS ONE)
Effective and safe pharmacological interventions for hyperlipidemia remains badly needed. By incorporating the key pharmacophore of fibrates into the natural scaffold of resveratrol, a novel structural compound ZBH was constructed. In present study, we found ZBH reserved approximately one third of the sirtuin 1 (SIRT1) activation produced by resveratrol at in-vitro enzyme activity assay, directly bound to and activated all three peroxisome proliferator-activated receptor (PPAR) subtypes respectively in PPAR binding and transactivation assays. Moreover, ZBH (EC₅₀, 1.75 µM) activate PPARα 21 fold more efficiently than the well-known PPAR pan agonist bezafibrate (EC₅₀ 37.37 µM) in the cellular transactivation assays. In the high fat diet induced hyperlipidemic hamsters, 5-week treatment with ZBH significantly lowered serum triglyceride, total cholesterol, LDL-C, FFA, hyperinsulinemia, and improved insulin sensitivity more potently than bezafibrate. Meanwhile, serum transaminases, creatine phosphokinase and CREA levels were found not altered by ZBH intervention. Mechanism study indicated ZBH promoted the expression of PPARα target genes and SIRT1 mRNA. Hepatic lipogenesis was markedly decreased via down-regulation of lipogenic genes, and fatty acid uptake and oxidation was simultaneously increased in the liver and skeletal muscle via up-regulation of lipolysis genes. Glucose uptake and utilization was also significantly promoted in skeletal muscle. These results suggested that ZBH significantly lowered hyperlipidemia and ameliorated insulin resistance more efficiently than bezafibrate in the hyperlipidemic hamsters primarily by activating of PPARα, and SIRT1 promotion and activation. ZBH thus presents a potential new agent to combat hyperlipidemia.